The cross-section of output and inflation in a dynamic stochastic general equilibrium model with sticky prices - Jörg Döpke; Michael Funke; Sean Holly; Sebastian Weber (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
In a standard dynamic stochastic general equilibrium framework, with sticky prices, the cross sectional distribution of output and inflation across a population of firms is studied. The only form of heterogeneity is confined to the probability that the ith changes its prices in response to a shock. In this Calvo setup the moments of the cross sectional distribution of output and inflation depend crucially on the proportion of firms that are allowed to change their prices. We test this model empirically using German balance sheet data on a very large population of firms. We find a significant counter-cyclical correlation between the skewness of inflation and aggregates, but the relation with output is less sure. Our results can be interpreted as indirect evidence of the importance of price stickiness in macroeconomic adjustments.
Keywords: D12; E52; E43; 330; New-Keynesian macroeconomics; DSGE; cross-sectional distribution; firm growth; Konjunktur; Inflation; Unternehmensentwicklung; Ungleichgewichtstheorie; Dynamisches Gleichgewicht; Preisrigidität; Theorie; Bilanz; Schätzung; Deutschland